Stress and self-regulation: Theoretical interaction problems - Grakauskas, Žygimantas (Psichologija, 2004)
During the last two decades more and more attention has been paid to the research of the phenomenon of self-regulation of behaviour. Human desire and ability to successfully regulate and control his behaviour has not just big theoretical but also practical, economic value, therefore the need of self-regulation laws practical application is increasing in such areas as health care, education, management of organizations.Self-regulation skills may also be successfully used for stress related problems solving as in other life spheres. However both on the level of theories and practically the interaction of self-regulation and stress phenomena is not completely clear and unambiguously understood. The purpose of this paper was to clarify the possibilities of creation of stress and self-regulation phenomena comprising theoretical model.We have defined behaviour self-regulation as the whole of internal and transactional processes, enabling the purposeful behaviour of individuals in time and in the presence of changing circumstances (Karoly, 1993).We have developed in detail the concept of self-regulation uniting various ideas of the authors of selfregulation paradigms (social-cognitive, cybernetic, dynamic, decision making) into one theoretical model, taking as the basis the feedback loop model suggested by cybernetic paradigm (Carver, Scheier, 1998).Stress has been described on the basis of R. S. Lazarus stress conception as the relation between the individual and environment, which threatens the personal wellbeing of the latter (Lazarus, Folkman, 1984), however instead of the concept of wellbeing we suggested to use the concept of goals. In such case they became the main connecting link between stress and self-regulation: the person is seeking self-regulation using the aid of self-regulation, and stress is raising barriers for these goals achievement.Further we have analysed certain stress and selfregulation interaction peculiarities. The major part of attention was directed to the dynamics of emotional reactions. Having assigned the transmission of informatikon as the main function, which is performed by them during the process of self-regulation, we defined three possible sources of this information during the time of stress. We also suppose that the emotions may also provide the information about what is the character of the goals, which are affected by stress. The other important question is the search of the methods for decreasing of negative stress influence on the selfregulation. In order to make them more productive we suggest to unite the researches carried out in the areas of coping and self-control, also to direct attention to the peculiarities of coping depending on the character of the pursued goals.In the further researches of stress and self-regulation we suggest to direct attention to the emotionalmotivational side of these effects’ interaction and try to explain how differing character of the goals (approach-avoidance) influences coping, how stress is influencing disengagement of goals or their revision, what the character of stress influence on various self-regulation processes is, how self-regulation is changing with the increasing stress strength, in case of its increase to the extreme and etc.
Keywords: stress; self-regulation